Вплив невпорядкованої атомної структури на швидкість оже-рекомбінації в InGaN сполуках p-типу - Zinovchuk, A. V.; Sevost’yanov, E. A. (Publishing house "Academperiodika", 2020)
The influence of the atomic disorder on the Auger recombination rate in p-InGaN alloys has been studied. The disorder was simulated using a 4 × 4 × 4 supercell in which In and Ga atoms taken in a required stoichiometric ratio were randomly distributed over the supercell sites. A comparison between the Auger recombination rates calculated in the framework of the supercell and virtual-crystal approximations showed that a large number of allowed interband transitions induced by the atomic disorder strongly increases the Auger recombination rate in wide-band-gap p-InGaN alloys.